Solar cell and preparation method thereof

By introducing an alumina layer into the solar cell to isolate the contact between the conductive layer and the perovskite material, the redox reaction problem caused by the failure of the self-assembled single-molecular layer is solved, and the stability and service life of the solar cell are improved.

CN119173053APending Publication Date: 2024-12-20TRINA SOLAR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411235389.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The self-assembled single-molecule layer has a risk of failure in solar cells, causing the perovskite light absorption layer to come into contact with the TCO substrate, causing a redox reaction to occur, and reducing the stability of the solar cell.

Method used

The alumina layer is introduced as a field passivation layer in the solar cell to isolate the contact between the first conductive layer and the perovskite material, and an alumina layer is provided between the first hole transport layer and the first conductive layer to prevent redox reaction.

Benefits of technology

It effectively improves the stability of solar cells, reduces the redox reaction between the conductive layer and the perovskite material after the failure of self-assembled single-molecular layer, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173053A_ABST
    Figure CN119173053A_ABST
Patent Text Reader

Abstract

The invention relates to a solar cell and a preparation method thereof. The solar cell comprises a first conductive layer, an aluminum oxide layer, a first hole transport layer, a perovskite light absorption layer and a second conductive layer which are arranged in sequence. Wherein the first hole transport layer is a self-assembled monomolecular layer. According to the solar cell, the self-assembly monomolecular layer is adopted between the first conductive layer and the perovskite light absorption layer to serve as the first hole transmission layer, holes can be selectively transmitted, the aluminum oxide layer is arranged between the first hole transmission layer and the first conductive layer, and the aluminum oxide layer can serve as a field passivation layer; the aluminum oxide is difficult to generate oxidation-reduction reaction with the perovskite material, so that the self-assembled monomolecular layer has a failure risk in the long-term operation process of the solar cell, and even if the self-assembled monomolecular layer fails, the aluminum oxide layer can also be used as a barrier layer to isolate the contact between the first conductive layer and the perovskite material; and the stability of the solar cell is prevented from being reduced due to an oxidation-reduction reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a solar cell and a preparation method thereof. Background Art

[0002] Organic and inorganic metal halide perovskite materials have the advantages of excellent photoelectric performance and low cost, and are suitable as light-absorbing layers of solar cells. In addition, the band gap of perovskite materials is adjustable, and they can be stacked with other photovoltaic materials such as crystalline silicon to form stacked solar cells, thereby achieving higher photoelectric conversion efficiency.

[0003] Perovskite solar cells usually have a hole transport layer between the TCO substrate and the perovskite light absorption layer. At present, the hole transport materials used in perovskite solar cells can be divided into inorganic hole transport materials and organic hole transport materials. Inorganic hole transport materials are mainly metal oxides such as nickel oxide, which have good stability themselves, but will undergo redox reactions when in contact with perovskite materials, and the stability of the two is poor after contact. Organic hole transport materials are mainly polymers and self-assembled monolayers (SAMs). It is difficult for polymers to form a uniformly covered film on a velvet substrate. As a single-molecule thin layer, the self-assembled monolayer can evenly cover the substrate, but during the long-term operation of the solar cell, the self-assembled monolayer has the risk of failure, resulting in the contact between the perovskite light absorption layer and the TCO substrate. The two react after contact, which also reduces the stability of the solar cell. Summary of the invention

[0004] Based on this, it is necessary to provide a solar cell and a method for preparing the same to solve the risk of failure of the self-assembled monolayer, which causes the perovskite light absorption layer to react with the TCO substrate and reduce the stability of the solar cell.

[0005] The first aspect of the present invention is to provide a solar cell, the scheme is as follows:

[0006] A solar cell, comprising:

[0007] a first conductive layer;

[0008] an aluminum oxide layer, disposed on the first conductive layer;

[0009] A first hole transport layer is arranged on a side of the aluminum oxide layer away from the first conductive layer, and the first hole transport layer is a self-assembled monolayer;

[0010] a perovskite light absorbing layer, disposed on a side of the first hole transport layer away from the aluminum oxide layer; and

[0011] The second conductive layer is disposed on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0012] In one embodiment, the thickness of the aluminum oxide layer is 0.1 nm to 5 nm.

[0013] In one embodiment, the solar cell further comprises:

[0014] The second hole transport layer is disposed between the first conductive layer and the aluminum oxide layer, and the second hole transport layer comprises a metal oxide hole transport material.

[0015] In one embodiment, the metal oxide hole transport material comprises doped or undoped NiO w , CuO2, CuO, CuAlO2, CuCrO2, WO3, MoO x 、V2O5、VO y CrO z At least one of the following, wherein w is 1-2, x is 0.5-3, y is 1-2.5, and z is 1-3.

[0016] In one embodiment, the second hole transport layer is a continuous phase dense structure.

[0017] In one embodiment, the second hole transport layer is a nanoparticle stacking structure.

[0018] In one embodiment, the thickness of the second hole transport layer is 2 nm to 200 nm.

[0019] In one embodiment, the self-assembled monolayer has a functional group and an anchoring group, the self-assembled monolayer is bonded to the aluminum oxide layer via the anchoring group, and the functional group has a dipole moment pointing to the aluminum oxide layer.

[0020] In one embodiment, the self-assembled monolayer is selected from at least one of the following general formulas (1) to (3):

[0021] (1)

[0022] (2)

[0023] (3);

[0024] Among them, R1, R2, R9, R 10 are independently selected from -H, C1~C4 alkyl, C1~C4 alkoxy, benzene ring or -X, X is a halogen atom; R3, R5, R 11 are independently selected from C1~C4 alkyl; R7 and R8 are independently selected from -H, -CH3, -C2H5; R4, R6, R12 Independently selected from phosphonic acid, carboxylic acid, cyanoacetic acid or cyanophosphonic acid.

[0025] In one embodiment, the material of the first conductive layer includes one or more of indium tin oxide, aluminum-doped zinc oxide, indium-doped zinc oxide, fluorine-doped tin oxide, indium tungsten oxide and indium cerium oxide.

[0026] In one embodiment, the perovskite light absorption layer comprises a perovskite material ABX3; wherein A comprises one or more of cesium ions, rubidium ions, potassium ions, methylamine ions, formamidine ions, methylenediamine ions, benzamidine cations and guanidine cations; B comprises one or more of lead ions, copper ions, zinc ions, gallium ions, tin ions and calcium ions; and X comprises one or more of fluoride ions, chloride ions, bromide ions, iodide ions, thiocyanate ions, tetrafluoroborate ions, hexafluorophosphate ions, formate ions and acetate ions.

[0027] In one embodiment, the material of the second conductive layer includes one or more of Au, Ag and Cu.

[0028] The first aspect of the present invention is to provide a method for preparing a solar cell according to any one of the above embodiments, the scheme is as follows:

[0029] A method for preparing a solar cell comprises the following steps:

[0030] providing a first conductive layer;

[0031] forming an aluminum oxide layer on the first conductive layer;

[0032] forming a first hole transport layer on a side of the aluminum oxide layer away from the first conductive layer;

[0033] forming a perovskite light absorbing layer on a side of the first hole transport layer away from the aluminum oxide layer; and

[0034] A second conductive layer is formed on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0035] In one embodiment, before forming the aluminum oxide layer, the preparation method further includes the following steps:

[0036] forming a second hole transport layer on the first conductive layer, wherein the second hole transport layer comprises a metal oxide hole transport material;

[0037] The aluminum oxide layer is formed on a side of the second hole transport layer away from the first conductive layer.

[0038] Compared with the traditional solution, the above solar cell and its preparation method have the following beneficial effects:

[0039] The above-mentioned solar cell uses a self-assembled monolayer as the first hole transport layer between the first conductive layer and the perovskite light absorption layer. The self-assembled monolayer can selectively transport holes. The self-assembled monolayer can evenly cover the substrate, and an aluminum oxide layer is arranged between the first hole transport layer and the first conductive layer. The aluminum oxide layer can serve as a field passivation layer. Moreover, aluminum oxide is different from other metal oxides and it is difficult for it to undergo redox reactions with perovskite materials. During the long-term operation of the solar cell, the self-assembled monolayer is at risk of failure. Even after the self-assembled monolayer fails, the aluminum oxide layer can serve as a barrier layer to isolate the first conductive layer from contact with the perovskite material, thereby preventing the redox reactions between the two from reducing the stability of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] FIG1 is a schematic structural diagram of a solar cell according to an embodiment;

[0041] FIG. 2 is a schematic structural diagram of a solar cell according to another embodiment. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0044] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0046] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0047] The term "alkyl" refers to a saturated hydrocarbon containing primary carbon atoms, secondary carbon atoms, tertiary carbon atoms, quaternary carbon atoms, or a combination thereof. Phrases containing this term, for example, "C1-C4 alkyl" refers to an alkyl containing 1 to 4 carbon atoms, and each occurrence may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl. Alkyl groups may be straight-chain or branched. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3).

[0048] The term "alkoxy" refers to a group having an -O-alkyl group, i.e., an alkyl group as defined above is connected to a parent core structure via an oxygen atom. A phrase comprising the term, for example, "C1~C4 alkoxy" refers to an alkyl group containing 1 to 4 carbon atoms, each occurrence of which can be independently of each other a C1 alkoxy group, a C4 alkoxy group, or a C5 alkoxy group. Alkoxy groups can be linear or branched. Suitable examples include, but are not limited to, methoxy (-O-CH3 or -OMe), ethoxy (-O-CH2CH3 or -OEt) and tert-butoxy (-OC(CH3)3 or -OtBu).

[0049] As shown in FIG. 1 , a solar cell 100 according to an embodiment includes a first conductive layer 110 , an aluminum oxide layer 120 , a first hole transport layer 130 , a perovskite light absorbing layer 140 , and a second conductive layer 150 .

[0050] The aluminum oxide layer 120 is disposed on the first conductive layer 110. The first hole transport layer 130 is disposed on the side of the aluminum oxide layer 120 away from the first conductive layer 110, and the first hole transport layer 130 is a self-assembled monolayer (SAMs). The perovskite light absorption layer 140 is disposed on the side of the first hole transport layer 130 away from the aluminum oxide layer 120. The second conductive layer 150 is disposed on the side of the perovskite light absorption layer 140 away from the first hole transport layer 130.

[0051] The above-mentioned solar cell 100 uses a self-assembled monolayer as the first hole transport layer 130 between the first conductive layer 110 and the perovskite light absorption layer 140. The self-assembled monolayer can selectively transport holes, and an aluminum oxide layer 120 is arranged between the first hole transport layer 130 and the first conductive layer 110. The aluminum oxide layer 120 can serve as a field passivation layer, and aluminum oxide is different from other metal oxides and it is difficult for aluminum oxide to undergo redox reaction with perovskite materials.

[0052] As a thin monomolecular layer, the self-assembled monolayer can evenly cover the substrate, but during the long-term operation of the solar cell 100, the self-assembled monolayer is at risk of failure. Due to the presence of the aluminum oxide layer 120, even after the self-assembled monolayer fails, the aluminum oxide layer 120 can still serve as a barrier layer to isolate the first conductive layer 110 from the perovskite material, thereby preventing the redox reaction between the two and reducing the stability of the solar cell 100.

[0053] Optionally, the material of the first conductive layer 110 may be a conductive metal oxide, for example, one or more of but not limited to indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), indium-doped zinc oxide (IZO), fluorine-doped tin oxide (FTO), indium tungsten oxide (IWO), indium cerium oxide (ICO) and the like.

[0054] The aluminum oxide layer 120 is preferably a dense layer. During the long-term operation of the solar cell 100, the self-assembled monolayer has the risk of failure. After the self-assembled monolayer fails, the dense aluminum oxide layer 120 can better isolate the contact between the conductive metal oxide in the first conductive layer 110 and the perovskite material, preventing the redox reaction between the two and reducing the stability of the solar cell 100.

[0055] The aluminum oxide layer 120 is preferably an ultra-thin layer, and the ultra-thin thickness design can provide conditions for the tunneling of carriers.

[0056] For example, in some examples, the thickness of the aluminum oxide layer 120 is 0.1 nm to 5 nm. Further, in some examples, the thickness of the aluminum oxide layer 120 is 0.5 nm to 3 nm. In some specific examples, the thickness of the aluminum oxide layer 120 is 0.1 nm, 0.3 nm, 0.5 nm, 0.8 nm, 1 nm, 1.3 nm, 1.5 nm, 1.8 nm, 2 nm, 2.3 nm, 2.5 nm, 2.8 nm, 3 nm, 3.3 nm, 3.5 nm, 3.8 nm, 4 nm, 4.3 nm, 4.5 nm, 4.8 nm, 5 nm, etc.

[0057] The perovskite light absorbing layer 140 includes a perovskite material (ABX3). A is a monovalent cation, including but not limited to one or more of cesium ions, rubidium ions, potassium ions, methylamine ions, formamidine ions, methylenediamine ions, benzamidine ions, and guanidine cations. B is a divalent cation, including but not limited to one or more of lead ions, copper ions, zinc ions, gallium ions, tin ions, and calcium ions. X is a monovalent anion, including but not limited to one or more of fluoride ions, chloride ions, bromide ions, iodide ions, thiocyanate ions, tetrafluoroborate ions, hexafluorophosphate ions, formate ions, and acetate ions.

[0058] In some examples, the thickness of the perovskite light absorbing layer 140 is 20 nm to 2000 nm. Further, in some examples, the thickness of the perovskite light absorbing layer 140 is 100 nm to 1500 nm. Further, in some examples, the thickness of the perovskite light absorbing layer 140 is 30 nm to 600 nm. In some specific examples, the thickness of the perovskite light absorbing layer 140 is 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, 2000 nm, etc.

[0059] Optionally, the material of the second conductive layer 150 may be, but is not limited to, one or more of metals such as Au, Ag, and Cu.

[0060] As shown in Fig. 1, in some examples, the solar cell 100 further includes a second hole transport layer 160. The second hole transport layer 160 is disposed between the first conductive layer 110 and the aluminum oxide layer 120, and the second hole transport layer 160 includes a metal oxide hole transport material.

[0061] In the above example, a second hole transport layer 160 is further arranged between the first conductive layer 110 and the aluminum oxide layer 120. The second hole transport layer 160 contains a metal oxide hole transport material, which cooperates with the self-assembled monolayer to further improve the selective transport effect of holes. Even after the self-assembled monolayer fails, efficient selective hole transport can be guaranteed. The aluminum oxide layer 120 can serve as a field passivation layer and a barrier layer to isolate the metal oxide hole transport material in the second hole transport layer 160 from contact with the perovskite material, thereby preventing the redox reaction between the two and reducing the stability of the solar cell 100.

[0062] Optionally, the metal oxide hole transport material may be, but is not limited to, nickel oxide, metal element doped or undoped NiO w (w is 1~2), CuO2, CuO, CuAlO2, CuCrO2, WO3, MoO x (x is 0.5~3), V2O5, VO y (y is 1~2.5), CrO z (z is 1~3) One or more.

[0063] The doped element in the metal oxide is a metal element, which may be one or more of, but not limited to, copper, lithium, cesium, magnesium, etc. For example, the doped nickel oxide may be one or more of, but not limited to, copper-doped nickel oxide, lithium-doped nickel oxide, cesium-doped nickel oxide, and magnesium-doped nickel oxide.

[0064] In some examples, the second hole transport layer 160 is a continuous phase dense structure. For example, the second hole transport layer 160 is prepared by evaporation, magnetron sputtering, atomic layer deposition, or other processes, and there is no gap in the second hole transport layer 160 .

[0065] In addition, the second hole transport layer 160 may also be a nanoparticle stacking structure, for example, the second hole transport layer 160 may be prepared by a solution method, and there may be gaps between the nanoparticles. Specifically, the nanoparticles are dispersed in a solvent to prepare a solution, and the solution is applied to a substrate and dried to form a film.

[0066] In some examples, the thickness of the second hole transport layer 160 is 2 nm to 200 nm. Further, in some examples, the thickness of the second hole transport layer 160 is 10 nm to 150 nm. Further, in some examples, the thickness of the second hole transport layer 160 is 10 nm to 30 nm. In some specific examples, the thickness of the second hole transport layer 160 is 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, etc.

[0067] The self-assembled monolayer has a functional group and an anchoring group. The anchoring group can be bonded to a substrate, such as the aluminum oxide layer 120. After the self-assembled monolayer is bonded to the aluminum oxide layer 120 through the anchoring group, the functional group has a dipole moment pointing to the aluminum oxide layer 120.

[0068] Optionally, the anchoring group may include but is not limited to at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, and cyanophosphonic acid. The anchoring group enables the SAM material to have good self-assembly ability, can form a good bond with the substrate, and enhances the interaction with the substrate.

[0069] Optionally, the functional group may include but is not limited to at least one of carbazole, dibenzocarbazole, and acridine.

[0070] In some examples, the self-assembled monolayer is selected from at least one of the following formulae (1) to (3):

[0071] (1)

[0072] (2)

[0073] (3);

[0074] Among them, R1, R2, R9, R 10 are independently selected from -H, C1~C4 alkyl, C1~C4 alkoxy, benzene ring or -X, X is a halogen atom; R3, R5, R 11 are independently selected from C1~C4 alkyl; R7 and R8 are independently selected from -H, -CH3, -C2H5; R4, R6, R 12 Independently selected from phosphonic acid, carboxylic acid, cyanoacetic acid or cyanophosphonic acid.

[0075] Furthermore, R1, R2, R9, R 10 are independently selected from -OCH3 or -X, X is a halogen atom. Further, R1, R2, R9, R 10 Independently selected from -OCH3 or -Br. The above groups match the structural energy level of the main group, so that the material has a good hole extraction ability.

[0076] Furthermore, R3, R5, R 11 Independently selected from -C2H4- or -C4H8-. The above groups match the structural energy level of the main group, so that the material has a good hole extraction ability.

[0077] Further, R7 and R8 are independently selected from -H or -CH3. Further, R7 and R8 are -CH3. The above groups match the structural energy level of the main group, so that the material has good hole extraction ability.

[0078] Furthermore, R4, R6, R 12 Independently selected from phosphonic acid or cyanophosphonic acid. The above groups have multiple active sites, can enhance the interaction with the substrate, and have a better anchoring effect.

[0079] For example, the self-assembled monolayer includes, but is not limited to, [6-(9H-carbazol-9-yl)hexyl]phosphonic acid (6PACz), [1-(9H-carbazol-9-yl)methyl]phosphonic acid (1PACz), [2-(9H-carbazol-9-yl)ethyl]phosphonic acid (2PACz), [3-(9H-carbazol-9-yl)propyl]phosphonic acid (3PACz), [4-(9H-carbazol-9-yl)butyl]phosphonic acid (4PACz), [8-(9H-carbazol-9-yl)octyl]phosphonic acid (8PACz), [4-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)butyl]phosphonic acid (4PABCz), [2-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)butyl]phosphonic acid (4PABCz), [ )ethyl]phosphonic acid (2PABCz), [4-(diphenylamino)phenyl)propyl]phosphonic acid (TPA-3PA), [4-(diphenylamino)phenyl)ethyl]phosphonic acid (TPA-2PA), [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphonic acid (2Br-6PACz), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACz), [3-(3,6-dimethyl-9H-carbazole-9-yl)propyl]phosphonic acid (Me-3PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Me-6PACz), [8-(3,6-dimethyl-9H-carbazole-9-yl) octyl]phosphonic acid (Me-8PACz), [1-(3,6-di-tert-butyl-9H-carbazole-9-yl)methyl]phosphonic acid (tBu-1PACz), [2-(3,6-di-tert-butyl-9H-carbazole-9-yl)ethyl]phosphonic acid (tBu-2PACz), [3-(3,6-di-tert-butyl-9H-carbazole-9-yl)propyl]phosphonic acid (tBu-3PACz), [4-(3,6-di-tert-butyl-9H-carbazole-9-yl)butyl]phosphonic acid (tBu-4PACz), [6-(3,6-di-tert-butyl-9H-carbazole-9-yl)hexyl]phosphonic acid (tBu-1PACz), [8-(3,6-di-tert-butyl-9H-carbazole-9-yl)octyl]phosphonic acid ( tBu-8PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)methyl]phosphonic acid (Ph-1PACz), [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Ph-2PACz), [3-(3,6-diphenyl-9H-carbazole-9-yl)propyl]phosphonic acid (Ph-3PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphonic acid (Ph-8PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphonic acid (Ph-8PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphonic acid (Ph-8PACz).6-dibromo-9H-carbazole-9-yl)butyl]phosphonic acid (2Br-4PACz), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid (4PADCB), [2-(7H-dibenzocarbazole-7-yl)ethyl]phosphonic acid (2PADCB), [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid (MeO-6PACz), [4-(N,N-di(4-methoxyphenylamino)phenyl)propyl]phosphonic acid (MeO-TPA-3PA), [2-(10H-phenoxazine-10-yl)ethyl]phosphonic acid (2PAPXZ), [1-(3,6-dimethyl-9H-carbazole-9-yl)methyl]phosphonic acid ( Me-1PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid (2Br-4PADMAc), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid, [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid.

[0080] As shown in FIG. 1 , in some examples, the solar cell 100 further includes an electron transport layer 170 . The electron transport layer 170 is disposed between the perovskite light absorbing layer 140 and the second conductive layer 150 .

[0081] Optionally, the material of the electron transport layer 170 may be, but is not limited to, ZnO (zinc oxide), SnO2 (tin oxide), TiO2 (titanium dioxide), SrTiO3 (strontium titanate), Zn2SnO4 (zinc stannate), ZrO2 (zirconium dioxide), Al2O3 (aluminum oxide), WO3 (tungsten trioxide), CeO x (cesium oxide), CdS (cadmium sulfide), CdSe (cadmium selenide), BaSnO3 (barium stannate), Nb2O5 (niobium pentoxide), C 60 (Fullerene), C 70 , PCBM (fullerene derivative) or more.

[0082] In some examples, the thickness of the electron transport layer 170 is 1 nm to 30 nm. Further, in some examples, the thickness of the electron transport layer 170 is 5 nm to 20 nm. In some specific examples, the thickness of the electron transport layer 170 is 2 nm, 5 nm, 8 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 27 nm, 29 nm, 30 nm, etc.

[0083] The solar cell may be a single-layer perovskite cell or a tandem cell, wherein the tandem cell may be, for example, a perovskite / crystalline silicon tandem cell, a full perovskite tandem cell, a perovskite / organic tandem cell, a perovskite / CIGS tandem cell, a perovskite / CdTe tandem cell, a perovskite / GaAs tandem cell, etc.

[0084] For example, the solar cell 200 shown in FIG2 is a perovskite / crystalline silicon stacked cell, which includes a transparent electrode layer 201, a first doped layer 202, a first amorphous silicon layer 203, a single crystal silicon substrate 204, a second amorphous silicon layer 205, a second doped layer 206, a first conductive layer 207, a second hole transport layer 208, an aluminum oxide layer 209, a first hole transport layer 210, a perovskite light absorption layer 211, an electron transport layer 212, a buffer layer 213, a second conductive layer 214, and an anti-reflection layer 215. A first grid line 216 is disposed on the anti-reflection layer 215, and a second grid line 217 is disposed on the transparent electrode layer 201.

[0085] It is understandable that the solar cell may also include other functional layers, such as a hole blocking layer, an electron blocking layer, etc. Those skilled in the art may supplement the structural features of the solar cell based on the aforementioned technical features as needed when implementing the present invention.

[0086] Furthermore, the present invention also provides a method for preparing any of the solar cells described above.

[0087] A method for preparing a solar cell according to an embodiment of the present invention comprises the following steps:

[0088] Step S1, providing a first conductive layer.

[0089] Step S2, forming an aluminum oxide layer on the first conductive layer.

[0090] Step S3, forming a first hole transport layer on a side of the aluminum oxide layer away from the first conductive layer.

[0091] Step S4, forming a perovskite light absorption layer on a side of the first hole transport layer away from the aluminum oxide layer.

[0092] Step S5, forming a second conductive layer on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0093] In some examples, before forming the aluminum oxide layer (step S2), the method for preparing a solar cell further includes the following steps:

[0094] A second hole transport layer is formed on the first conductive layer, wherein the second hole transport layer comprises a metal oxide hole transport material.

[0095] In this example, the aluminum oxide layer is formed on a side of the second hole transport layer away from the first conductive layer.

[0096] In some examples, before forming the second conductive layer (step S5), the method for preparing a solar cell further includes the following steps:

[0097] An electron transport layer is formed on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0098] In this example, the second conductive layer is formed on a side of the electron transport layer away from the first hole transport layer.

[0099] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods, and does not limit the content and protection scope of the present invention.

[0100] Example 1

[0101] The method for preparing a solar cell provided in this embodiment comprises the following steps:

[0102] Step 1, obtain ITO conductive glass with a size of 2.5 cm×2.5 cm, wash and dry it, and then treat it in an ultraviolet and ozone environment for 20 minutes to obtain a first conductive layer.

[0103] Step 2: Aluminum oxide is deposited on the first conductive layer using an ALD process. After three cycles of deposition, aluminum oxide with a thickness of about 0.3 nm is formed. The aluminum oxide is then treated in an ultraviolet and ozone environment for 1 min to obtain an aluminum oxide layer.

[0104] Step 3, prepare 2PACz solution, the solvent is ethanol and DMF with a volume ratio of 97:3, and the concentration is 0.5 mg / mL. In a nitrogen glove box, the 2PACz solution is first applied to the aluminum oxide layer, and after 30 seconds, it is spin-coated at a speed of 4000 rpm for 10 seconds, and then annealed at 100 ° C for 10 minutes, washed with ethanol, and annealed again at 100 ° C for 5 minutes to obtain a SAM material layer.

[0105] Step 4, prepare the perovskite precursor solution, the solvent is DMF and DMSO with a volume ratio of 4:1, CsI, FAI, PbI2 and PbBr2 are added to the solvent according to the concentration of Pb of 1.5 M, and 60 mg / mL of methyl ammonium chloride (MACl) is added and stirred for 6 h. In a nitrogen glove box, the perovskite precursor solution is applied to the above SAM material layer, first spin-coated at 500 rpm for 5 s, then spin-coated at 4000 rpm for 50 s, and then spin-coated at 5000 rpm for 40 s, chlorobenzene is flushed to the substrate surface, and then annealed at 120 ° C for 20 min to prepare the perovskite material FA. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3, and obtain a perovskite light absorbing layer.

[0106] Step 5: Prepare a 1,3-propylenediamine hydroiodide solution, using isopropanol as the solvent and a concentration of 0.5 mg / mL. In a nitrogen glove box, apply the 1,3-propylenediamine hydroiodide solution to the perovskite light absorption layer, spin-coat at 4000 rpm for 30 s, and then anneal at 100 °C for 2 min to obtain a passivation layer.

[0107] Step 6: C60 with a thickness of 30 nm is deposited on the passivation layer by a thermal evaporation process to obtain an electron transport layer.

[0108] Step 7: Deposit BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) with a thickness of 6 nm on the electron transport layer by a thermal evaporation process to obtain a hole blocking layer.

[0109] Step 8: Deposit metal Ag with a thickness of 200 nm on the hole blocking layer by thermal evaporation to obtain a second conductive layer.

[0110] Example 2

[0111] The method for preparing a solar cell provided in this embodiment comprises the following steps:

[0112] Step 1, obtaining an N-type silicon wafer, and performing a cleaning and texturing process on the N-type silicon wafer.

[0113] Step 2: Prepare a front intrinsic amorphous silicon layer and an N-type amorphous silicon layer on one side of the N-type silicon wafer using a PECVD process, with a total thickness of 25 nm.

[0114] Step 3: Prepare a back intrinsic amorphous silicon layer and a P-type amorphous silicon layer on the other side of the N-type silicon wafer using a PECVD process, with a total thickness of 20 nm.

[0115] Step 4: depositing metal oxide ITO on the N-type amorphous silicon layer by a sputtering process to form a front transparent conductive layer with a thickness of 10 nm.

[0116] Step 5, using the ALD process to deposit aluminum oxide on the front transparent conductive layer, after three cycles of deposition, to form aluminum oxide with a thickness of about 0.3 nm, and then treat it in an ultraviolet and ozone environment for 1 min to obtain an aluminum oxide layer.

[0117] Step 6, prepare 2PACz solution, the solvent is ethanol and DMF with a volume ratio of 97:3, and the concentration is 0.5 mg / mL. In a nitrogen glove box, the 2PACz solution is first applied to the aluminum oxide layer, and after 30 seconds, it is spin-coated at a speed of 4000 rpm for 10 seconds, and then annealed at 100 ° C for 10 minutes, washed with ethanol, and annealed again at 100 ° C for 5 minutes to obtain a SAM material layer.

[0118] Step 7, prepare the perovskite precursor solution, the solvent is DMF and DMSO with a volume ratio of 4:1, CsI, FAI, PbI2 and PbBr2 are added to the solvent according to the concentration of Pb of 1.5 M, and 60 mg / mL of methyl ammonium chloride (MACl) is added and stirred for 6 h. In a nitrogen glove box, the perovskite precursor solution is applied to the above SAM material layer, first spin-coated at 500 rpm for 5 s, then spin-coated at 4000 rpm for 50 s, and then spin-coated at 5000 rpm for 40 s, chlorobenzene is flushed to the substrate surface, and then annealed at 120 ° C for 20 min to prepare the perovskite material FA. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3, and obtain a perovskite light absorbing layer.

[0119] Step 8: Prepare a 1,3-propylenediamine hydroiodide solution, using isopropanol as the solvent and a concentration of 0.5 mg / mL. In a nitrogen glove box, apply the 1,3-propylenediamine hydroiodide solution to the perovskite light absorption layer, spin-coat at 4000 rpm for 30 s, and then anneal at 100 °C for 2 min to obtain a passivation layer.

[0120] Step 9: C60 with a thickness of 30 nm is deposited on the passivation layer by a thermal evaporation method to obtain a first electron transport layer.

[0121] Step 10: Deposit SnO2 with a thickness of 12 nm on the first electron transport layer by a thermal evaporation process to obtain a second electron transport layer.

[0122] Step 11, using thermal evaporation process to prepare silver grid lines on the front and back sides respectively, with a thickness of 400 nm.

[0123] Step 12, using a thermal evaporation process to deposit MgF2 with a thickness of 100 nm on the front side to form an anti-reflection layer.

[0124] Example 3

[0125] The method for preparing a solar cell provided in this embodiment comprises the following steps:

[0126] Step 1, obtain ITO conductive glass with a size of 2.5 cm×2.5 cm, wash and dry it, and then treat it in an ultraviolet and ozone environment for 20 minutes to obtain a first conductive layer.

[0127] Step 2: depositing a dense nickel oxide layer with a thickness of 15 nm on the first conductive layer by using a magnetron sputtering process.

[0128] Step 3, using the ALD process to deposit aluminum oxide on the nickel oxide layer, after three cycles of deposition, to form aluminum oxide with a thickness of about 0.3 nm, and then treat it in an ultraviolet and ozone environment for 1 min to obtain an aluminum oxide layer.

[0129] Step 4, prepare 2PACz solution, the solvent is ethanol and DMF with a volume ratio of 97:3, and the concentration is 0.5 mg / mL. In a nitrogen glove box, the 2PACz solution is first applied to the aluminum oxide layer, and after 30 seconds, it is spin-coated at a speed of 4000 rpm for 10 seconds, and then annealed at 100 ° C for 10 minutes, washed with ethanol, and annealed again at 100 ° C for 5 minutes to obtain a SAM material layer.

[0130] Step 5, prepare the perovskite precursor solution, the solvent is DMF and DMSO with a volume ratio of 4:1, CsI, FAI, PbI2 and PbBr2 are added to the solvent according to the concentration of Pb of 1.5 M, and 60 mg / mL of methyl ammonium chloride (MACl) is added and stirred for 6 h. In a nitrogen glove box, the perovskite precursor solution is applied to the above SAM material layer, first spin-coated at 500 rpm for 5 s, then spin-coated at 4000 rpm for 50 s, and then spin-coated at 5000 rpm for 40 s, chlorobenzene is flushed to the substrate surface, and then annealed at 120 ° C for 20 min to prepare the perovskite material FA. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3, and obtain a perovskite light absorbing layer.

[0131] Step 6: Prepare a 1,3-propylenediamine hydroiodide solution, using isopropanol as the solvent and a concentration of 0.5 mg / mL. In a nitrogen glove box, apply the 1,3-propylenediamine hydroiodide solution to the perovskite light absorption layer, spin-coat at 4000 rpm for 30 s, and then anneal at 100 °C for 2 min to obtain a passivation layer.

[0132] Step 7: C60 with a thickness of 30 nm is deposited on the passivation layer by a thermal evaporation process to obtain an electron transport layer.

[0133] Step 8: Deposit BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) with a thickness of 6 nm on the electron transport layer by a thermal evaporation process to obtain a hole blocking layer.

[0134] Step 9: Deposit metal Ag with a thickness of 200 nm on the hole blocking layer by thermal evaporation to obtain a second conductive layer.

[0135] Example 4

[0136] The steps for preparing the solar cell of this embodiment are basically the same as those of Embodiment 3, except that in step 2, the nickel oxide layer is prepared as follows:

[0137] Nickel oxide nanoparticles with a particle size of less than 20 nm were dispersed in deionized water to obtain a nickel oxide solution with a concentration of 15 mg / mL. After ultrasonication for 10 min, 50 μL of the nickel oxide solution was applied to the surface of the first conductive layer, spin-coated at 3000 rpm for 20 s, and then annealed at 100 °C for 10 min.

[0138] Comparative Example 1

[0139] The preparation steps of the solar cell of this comparative example are basically the same as those of Example 1, except that step 2 is not performed, that is, the aluminum oxide layer is not formed.

[0140] Comparative Example 2

[0141] The preparation steps of the solar cell of this comparative example are basically the same as those of Example 2, except that step 5 is not performed, that is, the aluminum oxide layer is not formed.

[0142] Comparative Example 3

[0143] The preparation steps of the solar cell of this comparative example are basically the same as those of Example 4, except that step 3 is not performed, that is, the aluminum oxide layer is not formed.

[0144] The performance of the solar cell prepared above was tested under standard test conditions, i.e., the air quality was AM1.5 G and the light intensity was 100 mW / cm 2, the temperature is 25 ℃. The solar cell performance test results are shown in Table 1.

[0145] Table 1 Performance parameters of solar cells tested under standard test conditions

[0146]

[0147] The battery was placed in an environment of 85 °C for 1000 h for aging treatment, and the performance of the solar cell after aging was tested. The test results are shown in Table 2.

[0148] Table 2 Performance parameters of solar cells after aging

[0149]

[0150] Compared with the corresponding comparative examples, in Examples 1, 2 and 4, an aluminum oxide layer is disposed between the first hole transport layer and the first conductive layer. The aluminum oxide layer can play a field passivation effect. From the results in Table 1, it can be seen that compared with the corresponding comparative examples, the open circuit voltage, fill factor and photoelectric conversion efficiency of the solar cell in Examples 1, 2 and 4 are all improved to a certain extent.

[0151] It can be seen from the results in Table 2 that after aging treatment, the electrical properties of the solar cell have all declined. One of the reasons is that the self-assembled monolayer as the first hole transport layer has the risk of failure under long-term high temperature. After the self-assembled monolayer fails, the metal oxide in the lower layer contacts the perovskite material and then undergoes redox reaction, which reduces the stability of the solar cell.

[0152] In the above embodiment, an aluminum oxide layer is arranged between the first hole transport layer and the first conductive layer. It is difficult for aluminum oxide to undergo redox reaction with the perovskite material. Even after the self-assembled monolayer fails, the aluminum oxide layer can serve as a barrier layer to isolate the first conductive layer from contact with the perovskite material, thereby preventing the redox reaction between the two and reducing the stability of the solar cell.

[0153] From the results in Table 2, it can be seen that the degree of decline in electrical performance of Examples 1, 2 and 4 is significantly reduced compared with the corresponding comparative examples. For example, after aging treatment, the short-circuit current of Example 1 decreased by 0.05%, the open-circuit voltage decreased by 1.64%, the fill factor decreased by 1.15%, and the photoelectric conversion efficiency decreased by 2.36%. While the short-circuit current of Comparative Example 1 decreased by 2.72%, the open-circuit voltage decreased by 4.95%, the fill factor decreased by 6.07%, and the photoelectric conversion efficiency decreased by 13.16%.

[0154] Compared with Example 1, Example 3 further provides a second hole transport layer between the first conductive layer and the aluminum oxide layer, which cooperates with the self-assembled monolayer to further improve the selective transport effect of holes. It can be seen from the test results in Tables 1 and 2 that the short-circuit current, open-circuit voltage, fill factor and photoelectric conversion efficiency of Example 3 are all improved compared with Example 1.

[0155] It can be seen from the results in Table 2 that after aging treatment, the degree of decline in the electrical properties of Examples 3 and 4 is less than that of Example 1. This is because the photothermal stability of nickel oxide is due to the self-assembled monolayer. Even after the self-assembled monolayer fails, nickel oxide can still maintain a good hole transport effect.

[0156] It can be seen from the results in Table 2 that after aging treatment, the degree of decline in the electrical performance of Comparative Example 3 is significantly greater than that of Comparative Example 1. This is because when the aluminum oxide layer is not provided, the reaction between nickel oxide and the perovskite material is intensified, resulting in a more obvious decline in the performance of the solar cell.

[0157] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0158] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A solar cell, characterized in that: include: a first conductive layer; an aluminum oxide layer, disposed on the first conductive layer; A first hole transport layer is arranged on a side of the aluminum oxide layer away from the first conductive layer, and the first hole transport layer is a self-assembled monolayer; A perovskite light absorbing layer, disposed on a side of the first hole transport layer away from the aluminum oxide layer; as well as The second conductive layer is disposed on a side of the perovskite light absorbing layer away from the first hole transport layer.

2. The solar cell according to claim 1, wherein: The thickness of the aluminum oxide layer is 0.1 nm to 5 nm.

3. The solar cell according to claim 1, wherein: The solar cell further comprises: The second hole transport layer is disposed between the first conductive layer and the aluminum oxide layer, and the second hole transport layer comprises a metal oxide hole transport material.

4. The solar cell according to claim 3, characterized in that The metal oxide hole transport material includes doped or undoped NiO w , CuO2, CuO, CuAlO2, CuCrO2, WO3, MoO x 、V2O5、VO y CrO z At least one of the following, wherein w is 1-2, x is 0.5-3, y is 1-2.5, and z is 1-3.

5. The solar cell according to claim 3, characterized in that: The solar cell meets one or more of the following characteristics (1) to (3): (1) The second hole transport layer is a continuous phase dense structure; (2) The second hole transport layer is a nanoparticle stacking structure; (3) The thickness of the second hole transport layer is 2 nm~200 nm.

6. The solar cell according to any one of claims 1 to 5, characterized in that The self-assembled monolayer has a functional group and an anchoring group. The self-assembled monolayer is bonded to the aluminum oxide layer through the anchoring group. The functional group has a dipole moment pointing to the aluminum oxide layer.

7. The solar cell according to claim 6, characterized in that The self-assembled monolayer is selected from at least one of the following general formulas (1) to (3): (1)、 (2)、 (3); Among them, R1, R2, R9, R 10 are independently selected from -H, C1~C4 alkyl, C1~C4 alkoxy, benzene ring or -X, X is a halogen atom; R3, R5, R 11 are independently selected from C1~C4 alkyl; R7 and R8 are independently selected from -H, -CH3, -C2H5; R4, R6, R 12 Independently selected from phosphonic acid, carboxylic acid, cyanoacetic acid or cyanophosphonic acid.

8. The solar cell according to any one of claims 1 to 5 and 7, characterized in that: The solar cell meets one or more of the following characteristics (1) to (3): (1) The material of the first conductive layer includes one or more of indium tin oxide, aluminum-doped zinc oxide, indium-doped zinc oxide, fluorine-doped tin oxide, indium tungsten oxide and indium cerium oxide; (2) The perovskite light absorption layer comprises a perovskite material ABX3; wherein A comprises one or more of cesium ions, rubidium ions, potassium ions, methylamine ions, formamidine ions, methylenediamine ions, benzamidine cations and guanidine cations; B comprises one or more of lead ions, copper ions, zinc ions, gallium ions, tin ions and calcium ions; X comprises one or more of fluoride ions, chloride ions, bromide ions, iodide ions, thiocyanate ions, tetrafluoroborate ions, hexafluorophosphate ions, formate ions and acetate ions; (3) The material of the second conductive layer includes one or more of Au, Ag and Cu.

9. A method for preparing a solar cell, characterized in that: The following steps are involved: providing a first conductive layer; forming an aluminum oxide layer on the first conductive layer; forming a first hole transport layer on a side of the aluminum oxide layer away from the first conductive layer, wherein the first hole transport layer is a self-assembled monolayer; forming a perovskite light absorbing layer on a side of the first hole transport layer away from the aluminum oxide layer; and A second conductive layer is formed on a side of the perovskite light absorbing layer away from the first hole transport layer.

10. The preparation method according to claim 9, characterized in that: Before forming the aluminum oxide layer, the preparation method further comprises the following steps: forming a second hole transport layer on the first conductive layer, wherein the second hole transport layer comprises a metal oxide hole transport material; The aluminum oxide layer is formed on a side of the second hole transport layer away from the first conductive layer.

Citation Information

Cited By

  • Inverse perovskite cell containing self-assembled monomolecular layer and preparation method thereof

    CN119968010A

  • Perovskite solar cell, preparation method thereof and power utilization device

    CN122094291A